Application possibilities of marketing strategy in construction companies (Economics and region, 2024)
The purpose of the analysis of the socio-economic environment is to determine the social and socio-economic aspects related to the development and evaluation of the project strategy and marketing concept. These aspects can reflect the society and its culture, social and economic situation, politics in the regions, as well as existing rules, traditions and customs, etc. The scope and depth of marketing research is determined by the complexity or novelty of the research. Determining the appropriate methods and means of conducting marketing research should be consistent with the objectives and limitations. A fairly important point in conducting research is the assessment of necessary and sufficient information. Since the collection of information itself has a high cost in the modern economy, its collection process requires adequate management. An external and internal analysis should be carried out in each specific project, but the base set, as a rule, remains the same. Market structure analysis is usually the identification and quantification of different market segments. At the same time, there are many models for the analysis of market segments, which are a combination of different criteria or directions for segmentation, market (structuring). Such criteria can be consumer segmentation: - with the benefit obtained from the use of the product; - through life; - gender and age; - geographic; - about the situations of consumers; - according to the rules (strategies) for the selection of goods; - brand loyalty; - due to price sensitivity; - using the classifiers of the sectors of the national economy; - according to the way you shop. Analysis of market capacity is aimed at predicting potential sales realistically in a certain place, determining the goods sold. When analyzing market capacity, it is very important to identify and account for seasonal or other fluctuations in sales. In our opinion, when choosing a strategy for the development of construction enterprises, it is necessary to be guided by a system of objective preconditions for the formulation of the main strategies, because real success depends not only on the rational organization of production, cost, but also on the reduction, resource efficiency, increase in labor productivity and other organizational and production factors, but also from the ability to adapt to the external environment, the needs of consumers, the competition of commodity producers, distribution channels and the movement of goods, ie. it also depends on the marketing strategy.
Keywords: construction enterprises; marketing strategy; intensive growth; intense; strategic changes; development strategy; strategic partnership; concept